Precancerous Cervical Lesion Among Adult Women With Human Immune Deficiency Virus on Anti Retroviral Therapy At Saint Peter Specialized Hospital, Ethiopia: A Hospital-Based Cross-Sectional Study - Zelalem, Wondimu; Weldegebreal, Fitsum; Ayele, Behailu Hawulte; Deressa, Alemayehu; Debella, Adera; Eyeberu, Addis; Hassen, Fila Ahmed; Dessie, Yadeta (Frontiers in Oncology, 2022)
Background Cervical cancer is the fourth most frequent cancer in women representing 6.6% of all female cancers occurring in low and middle-income countries, where resources for cancer prevention programs are often scarce. So this study aimed to assess the prevalence of precancerous cervical lesion and associated factors among adult women with human immune deficiency virus (HIV) on Anti Retroviral Therapy (ART) at Saint Peter Specialized Hospital, Addis Ababa, Ethiopia. Methods An institution-based cross-sectional study was conducted from November 06 to July 20, 2020 among 267 adult women with HIV on Anti Retroviral Therapy At Saint Peter Specialized Hospital, Ethiopia. Data were collected using face-to-face interview, patient chart review, and the examination of the squamo-columnar junction by the visual inspection with the acetic acid method. The collected data were entered into Epi-data version 3.1 and exported to Statistical Package for the Social Sciences (SPSS) version 24.0 for analysis. Bivariate and multivariable binary logistic regression analysis were used to identify factors associated with the precancerous cervical lesion. Statistical significance was considered at a P-valve less than 0.05. Result A total of 267 women who were on ART were included in the study and the prevalence of precancerous cervical lesion was 7.5% with 95% CI =4.10%-10.50%. Modern family planning (AOR = 4.14, 95% CI = 1.23-13.87), history of sexual transmission infection (STI) (AOR=5.39, 95% CI= 1.56-18.70) and viral load (AOR=20.85, 95% CI = 6.19-70.25) had significant association with precancerous cervical lesion Conclusion In this study, the prevalence of precancerous cervical lesion is relatively low compared to studies in low and middle-income countries. Modern family planning, history of sexual transmitted infection, and viral load had a significant association with a precancerous cervical lesion. Hence, encouraging modern family planning, and routine screening of women for pre-cancerous cervical lesions for those with high viral load have enormous contributions to decreasing cervical cancer disease among Women with Human Immune Deficiency Virus through Anti Retroviral Therapy.